2021
DOI: 10.1167/tvst.10.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic and Morphologic Strain Differences in a Low-Dose NaIO3-Induced Retinal Pigment Epithelium Damage Model

Abstract: We aimed to explore differences in the NaIO 3 -elicited responses of retinal pigment epithelium (RPE) and other retinal cells associated with mouse strains and dosing regimens.Methods: One dose of NaIO 3 at 10 or 15 mg/kg was given intravenously to adult male C57BL/6J and 129/SV-E mice. Control animals were injected with PBS. Morphologic and functional changes were characterized by spectral domain optical coherence tomography, electroretinography, histologic, and immunofluorescence techniques.Results: Injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(77 reference statements)
6
13
0
Order By: Relevance
“…As previously reported [ 24 , 25 ], we also confirmed that RPE damage resulting from NaIO 3 -induced oxidative stress in mice could be divided into three regions with distinct RPE morphologies, i.e., normal-appearing RPE (“normal RPE”) (periphery), elongated RPE (transitional zone), and severely damaged or lost RPE (center) ( Figure 1 ), which seemed to reflect the degrees of RPE damage. Indeed, we observed that the degree of retinal photoreceptor cell death was correlated with these three regions.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As previously reported [ 24 , 25 ], we also confirmed that RPE damage resulting from NaIO 3 -induced oxidative stress in mice could be divided into three regions with distinct RPE morphologies, i.e., normal-appearing RPE (“normal RPE”) (periphery), elongated RPE (transitional zone), and severely damaged or lost RPE (center) ( Figure 1 ), which seemed to reflect the degrees of RPE damage. Indeed, we observed that the degree of retinal photoreceptor cell death was correlated with these three regions.…”
Section: Resultssupporting
confidence: 90%
“…These are the periphery with normal hexagonal cells that have a cobblestone-like appearance, the transitional zone with elongated and enlarged cells that still have ZO-1 at cell junctions, and the center with severely damaged cells that are unrecognizable or lost. Similar observations have been described with NaIO 3 -induced RPE damage in several reports, and therefore these features seem common morphological changes caused by NaIO 3 [ 24 , 25 , 53 ]. It should be noted that although we call morphologically normal-appearing RPE as “normal RPE”, normal ZO-1 staining patterns do not indicate that the RPE is physiologically and functionally normal.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations